Photocatalytic activity of TiO2 film containing Fe2O3 via plasma electrolytic oxidation. (2nd June 2016) - Kim, Y. S.; Shin, K. R.; Kim, G. W.; Ko, Y. G.; Shin, D. H.
Abstract : This study investigated the photocatalytic activity of an Fe containing TiO2 film produced in the FePO4 electrolyte via the plasma electrolytic oxidation (PEO) method. For this purpose, the PEO process was carried out on titanium substrate under ac condition in two different alkaline electrolytes containing K3 PO4 and FePO4 respectively. The structure, chemical composition and constituent phases of the PEO treated samples were analysed via SEM, X-ray photoelectron spectroscopy and X-ray diffraction. The optical properties of the samples were also examined by an ultraviolet–visible spectrophotometer. In terms of the photocatalytic activity judging from the decomposition of methylene blue under visible light illumination, the sample formed in the FePO4 electrolyte was better than that in the K3 PO4 electrolyte due to the incorporation of an Fe compound that has a narrow band gap.